Pyloric obstruction due to gastric tuberculosis–an endoscopic diagnosis. Issue 771 (January 1990) - Gupta, B.; Mathew, S.; Bhalla, S.
Abstract : A 22 year old male presented with symptoms of gastric outlet obstruction. Endoscopy showed a hypertrophic nodular lesion around the pyloric opening with pyloric stenosis. The endoscopic biopsy and histopathological examination revealed tuberculosis involving the stomach, an extremely rare lesion.